Chemical Composition, Quality Indices and Viscosity of Edible Oils from Blends of African Oil Bean Seed Oil and Sesame Seed Oil - Onwuzuruike, Uzochukwu Anselm; Inyang, Ufot Evanson; Edima-Nyah, Anne Peter; Okwunodulu, Innocent N.; Anyanwu, Chioma Uchechi (PUI BiGME Universitas Jambi, 2024)
This study adopted the concept of blending in developing and evaluating the properties of binary oil blends from African oil bean seed oil and sesame seed oil. Vegetal oils were extracted from African oil bean seeds (AB) and sesame seeds (SS) through Soxhlet extraction and blended in the following proportions: AB100:SS0, AB0:SS100, AB90:SS10, AB80:SS20, AB70:SS30, AB60:SS40 and AB50:SS50 respectively. The chemical, quality and viscosity properties was investigated. Findings from this study showed that the chemical composition decreased from 124.55 to 101.28 g of I2/100 g, 208.67 to 191.29 mg KOH/g, 1.94 to 1.62% for iodine, saponification and unsaponifiable matter values while quality properties improved with reduction in PV, FFA, pAV, AV and totox value from 3.12 to 2.79 meq O2/kg, 4.04 to 2.99%, 0.57 to 0.31, 8.08 to 5.99 mg KOH/g and 6.81 to 5.88 respectively as the proportion of sesame seed oil increased in the blended oils from 10 to 50%. Viscosity results at 50C and 370C increased in the studied samples from 560.00 mPa.s in AB100:SS0 to 635.00 mPa.s in AB50:SS50 and from 91.00 mPa.s in AB100:SS0 to 103.00 mPa.s in AB50:SS50 respectively. Conclusively, binary oil blends had better oil properties and could be optimized for food applications